The Implementation of Pre-Reading Activities to Improve Senior High Schools Students’ Reading Comprehension - Letwory, Noura C; Latuheru, Henry (Program Studi Pendidikan Bahasa Inggris FKIP, Universitas Pattimura Ambon, 2024)
This study aims to describe the implementation of pre-reading activities in class X-3 SMA Negeri 2 Ambon to improve students’ reading comprehension. This research is a Classroom Action Research (CAR) which was conducted in several stages, such as; (1) planning the action (2) implementing the action, (3) Evaluation, and (4) Reflection. The subjects in this study were 36 students in class X-3 of SMA Negeri 2 Ambon. Instruments used in the form of observation, Study report, and questionnaire. The analysis used is qualitative analysis and quantitative analysis. The indicator of success in this research is when students are able to reach the indicator of success where 70 % of students get the score between 70-100. The results of this study indicate that Pre-reading activities help students to improve their reading comprehension towards a text and students give positive response toward the implementation of pre-reading activities.